2018
DOI: 10.1155/2018/7495081
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Urinary Tract Carcinoma among Subjects with Bladder Pain Syndrome/Interstitial Cystitis: A Nationwide Population-Based Study

Abstract: Objective To investigate the subsequent risks of urinary tract cancers among individuals with bladder pain syndrome/interstitial cystitis (BPS/IC), and gender differences, as well as the effect of associated comorbidity using a population-based administrative database in Taiwan. Patients and Methods BPS/IC subjects (10192) and their age- and sex-matched non-BPS/IC control subjects (30576), who had no previous upper urinary tract cancer (UUC), bladder cancer (BC), and prostate cancer (PC), subsequently develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
(28 reference statements)
1
11
0
2
Order By: Relevance
“…It means that cystoscopy has been carried out with findings of either glomerulation or the presence of Hunner's lesion. Therefore, we were confident that those patients diagnosed with IC by using the ICD‐9 code and who presented typical compatible cystoscopic findings were included in the present study . Different subtypes of IC have been identified, such as ulcer type, which might have distinct characteristics and underlying pathophysiology .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It means that cystoscopy has been carried out with findings of either glomerulation or the presence of Hunner's lesion. Therefore, we were confident that those patients diagnosed with IC by using the ICD‐9 code and who presented typical compatible cystoscopic findings were included in the present study . Different subtypes of IC have been identified, such as ulcer type, which might have distinct characteristics and underlying pathophysiology .…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, there was little possibility for anyone without a clear diagnosis of IC being eligible. The same methods for the enrollment of IC have already been applied in several published studies …”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Ueda et al indicated that IC/BPS is a common comorbidity among patients with refractory chronic prostatitis/chronic pelvic pain syndrome [ 18 ]. Additionally, a recent study of ours showed that IC/BPS patients are at risk of developing urinary tract cancer at later years [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was based on data from National Health Insurance Research Database (NHIRD) in Taiwan. The detailed information of NHIRD was described in our previous report [ 9 ]. Briefly, the NHI system was implemented from 1995 and has covered almost all population (98%) in Taiwan by the compulsory and universal health insurance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation